Programmable 3D Shape Changes in Liquid Crystal Polymer Networks of Uniaxial Orientation - Yu, Li; Shahsavan, Hamed; Rivers, Geoffrey; Zhang, Che; Si, Pengxiang; Zhao, Boxin (Advanced functional materials, 2018)
3D programmable materials are highly interesting and have a great potential to enable smart robotic devices. Stimuli‐responsive liquid crystal polymer networks (LCNs) offer an attractive platform for the design and fabrication of 3D programmable materials. To date, extensive efforts have been devoted to the design of 3D programmable LCNs by spatially modulating the orientation of liquid crystals. However, the practical application of LCN actuators has been elusive, partly due to tedious orientation technology and monotonous geometry. To resolve this issue, programmable 3D shape changes achieved in LCNs with uniaxial orientation and homogenous composition using a mechanical programming process inspired by the “programming process” of shape‐memory polymers are reported. The mechanical programming process is suitable for LCNs with distinct geometries, for example, the film and fiber, suggesting a promising way for the design of 3D programmable LCN actuators with complex geometries, and deformation profiles (buckle, helix, horn). Mechanical programming process inspired by the “programming process” of shape‐memory polymer is utilized to enable reversible, programmable, and complex 3D shape‐changing behavior in liquid crystal polymer networks (LCNs). The uniaxial orientation is sufficient to allow homogenous composition LCNs of distinct geometries such as the film and fiber to exhibit sophisticated deformation modes.